Perbandingan Sastra Dalam Puisi “Water Karya Koleka Putuma Dan Puisi Peringatan Karya Wiji Tukul” - Sylvia Friska Dara Citra; Erika Retnosari; Muhammad Rohman (PT. Padang Tekno Corp, 2025)
This study aims to conduct a comparative literature on two poetic works that have the theme of resistance against oppression, namely the poem